The concepts of crimen pessimum, delicta graviora, delicta reservata in canonical criminal law. A legal historical analysis - Kiełpiński, Krzysztof (Prawo Kanoniczne, 2026)
This article aims to present the development of canonical criminal law from a legal‑historical perspective by analysing three key concepts that have significantly influenced the creation and evolution of the catalogue of grave crimes in the law of the Catholic Church: crimen pessimum, delicta graviora and delicta reservata. Until now, both Polish and international scholarship has addressed these terms primarily in the context of specific research areas, particularly sexual abuse of minors by clerics, offences against the sacraments and the imposition of canonical penalties. In this study, the aforementioned concepts are examined systematically from a legal‑dogmatic and historical perspective, which makes it possible to show their nature, origin, evolution and their location within specific norms of canon law. The primary sources for this research include documents issued by the Holy See and the Codes of Canon Law of 1917 and 1983, along with the reform of Book VI of the 1983 Code, which was promulgated by the apostolic constitution Pascite gregem Dei in 2021. The literature has been subjected to critical analysis. The primary methodologies employed include dogmatic-legal analysis, legal-historical analysis, philology, linguistics, and analytical methods. The article presents recent research on the development of terms crimen pessimum, delicta graviora and delicta reservata, which has not yet been concisely presented in Polish scholarship. It contributes to a deeper understanding of the contemporary system of canonical criminal law, especially in relation to grave offences against faith, sacraments and morals.